Tree health assessment for roadside tree in Kota Kinabalu city Centre, Sabah - Andy R. Mojiol (Universiti Malaysia Sabah, 2018)
This study aimed to assess the health of main tree in the Kota Kinabalu City Centre, Sabah. In this study, principal evaluation standards were made by using visual observation of trees or Visual Tree Assessment (VTA). This study was conducted to identify any effect of damage or defect on trees via the observation of trees at their roots, stems, branches and leaves. There were five zones in the study area, namely from KK Lama and Jesselton Point (Zone 1) to Pasar Besar. The tree health parameters were evaluated from the presence of pests and diseases, trees health, foliage colour, the growth rate of trees, infections of the trees and potential failure of tree roots. In this study, nine of pathogens, pests and diseases of trees were observed, which were termites, fungi, aphid, mushrooms, epiphytes, parasites, ants, weeds and Whiteflies. This study showed that there were 23 species from the 688 stand of trees in the study area. The study found that the state average foliage colour was normal, a moderate growth rate and infection of the tree was still under controlled. The potential failure of tree root was found in low level as well. In a nutshell, the overall health of trees was found to be in good and moderate levels. This study was conducted as a reference in health detection of tree for The City Hall management (DBKK) and also as a reference for University students in conducting tree health assessment.